ChemInform Abstract: Transition‐Metal‐Free Synthesis of N‐(1‐Alkenyl)imidazoles by Potassium Phosphate‐Promoted Addition Reaction of Alkynes to Imidazoles. Issue 25 (24th June 2014) - Lu, Linhua; Yan, Hong; Liu, Defu; Rong, Guangwei; Mao, Jincheng
Abstract In contrast to the examined heterocyclic amines, aliphatic amines such as morpholine and diisopropylamine as well as aniline do not react under the investigated conditions.